Blues Harmonica For Dummies - Yerxa, Winslow (Hoboken, New Jersey John Wiley & Sons, 2012)
The fun and easy way to play blues on the harmonica Blues harmonica is the most popular and influential style of harmonica playing, and it forms the basis for playing harmonica in other styles such as rock and country
Include Illustration and Index
Keywords: Harmonica -- Blues (Music)--Instruction and study